1999
DOI: 10.1086/302416
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Gene for Sclerosteosis to the van Buchem Disease–Gene Region on Chromosome 17q12–q21

Abstract: Sclerosteosis is an uncommon, autosomal recessive, progressive, sclerosing, bone dysplasia characterized by generalized osteosclerosis and hyperostosis of the skeleton, affecting mainly the skull and mandible. In most patients this causes facial paralysis and hearing loss. Other features are gigantism and hand abnormalities. In the present study, linkage analysis in two consanguineous families with sclerosteosis resulted in the assignment of the sclerosteosis gene to chromosome 17q12-q21. This region was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 25 publications
2
71
0
1
Order By: Relevance
“…The mutations do not have any effect on the functioning of the protein but rather disrupt the ligand binding of the extracellular inhibitors DKK1 and sclerostin (120,121,122), in which a short binding motif was found by structure analysis (123). The latter protein was identified by positional cloning for two other sclerosing bone disorders, Van Buchem disease and sclerosteosis (124,125,126,127). The radiographic picture in these patients is very reminiscent to HBM.…”
Section: Identification Of the Role Of The Lrp5 Gene In Bonementioning
confidence: 99%
“…The mutations do not have any effect on the functioning of the protein but rather disrupt the ligand binding of the extracellular inhibitors DKK1 and sclerostin (120,121,122), in which a short binding motif was found by structure analysis (123). The latter protein was identified by positional cloning for two other sclerosing bone disorders, Van Buchem disease and sclerosteosis (124,125,126,127). The radiographic picture in these patients is very reminiscent to HBM.…”
Section: Identification Of the Role Of The Lrp5 Gene In Bonementioning
confidence: 99%
“…Sclerosteosis differs from van Buchem disease because it is more severe and is associated with hand malformations such as syndactyly, absent or dysplastic nails, and radial deviation of the terminal phalanges (Balemans et al 2005). Both diseases were mapped to the same region of chromosome 17q12-21 in the late 1990s (Van Hul et al 1998;Balemans et al 1999), and positional cloning studies identified recessive loss-of-function mutations in Sclerostin (SOST) gene as the cause of Sclerosteosis in 2001 (Balemans et al 2001;Brunkow et al 2001). Interestingly, mutation screening of SOST in patients with van Buchem disease showed no mutations, but a homozygous 52-Kb deletion was identified 35 Kb downstream from SOST as the cause of this condition (Balemans et al 2002b).…”
Section: Sclerostinmentioning
confidence: 99%
“…In humans, lack of sclerostin causes sclerosteosis, a generalized skeletal hyperostosis disorder that results from elevated Wnt signaling/osteoblast activity [108,135], while non-coding deletions of gene regulatory regions that control SOST expression result in similar phenotypes [83,88]. In animal models, overexpression of human SOST causes osteopenia and limb defects [136,137], while lack of Sost in knockout mice causes 3-4 times more bone mass, consistent with human phenotypes [83].…”
Section: Introductionmentioning
confidence: 67%